Ethical Reflection as an Element of Moral Culture of Personality - Kobliakovas, Valentinas (Problemos, 1979)
In the article attention is drawn to the significance of ethical reflection and ethical world-outlook in the development of moral culture of personality. It is pointed out that ethical culture is acquired by man not only and not so much through the element of moral life as through moral-ethical reflexivity.